Suberin biotech potential: from bactericidal nanoparticles to optical sensors. - Rodrigues, Rúben Miguel Lopes (2021)
"With the increased exposure to antibiotics and the matching selective pressure that it imposes, bacteria naturally have evolved to develop resistance to several antibiotics and, in the worst cases, multi drug resistance. This seriously affects the treatment of bacterial infections and the problem worsens when considering that the development of new antibiotic molecules is increasingly difficult and costly. Consequently, alternative antibacterial substances are being increasingly sought out, where antimicrobial lipids are being pointed as a promising solution. Fatty acids and monoglycerides are natural substances that possess antimicrobial properties, capable of destabilizing cell membranes, while causing several direct and indirect inhibitory effects, such as impairment of nutrient uptake, generation of peroxidation and auto-oxidation degradation products or direct lysis of bacterial cells and inhibition of enzyme activity. More importantly, evolution of resistant phenotypes is increasingly difficult. "